2008
DOI: 10.1152/ajpendo.00586.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced expression of the glucocorticoid response gene lipocalin 2 in chondrocytes

Abstract: Owen HC, Roberts SJ, Ahmed SF, Farquharson C. Dexamethasone-induced expression of the glucocorticoid response gene lipocalin 2 in chondrocytes. Am J Physiol Endocrinol Metab 294: E1023-E1034, 2008. First published April 1, 2008 doi:10.1152/ajpendo.00586.2007 are commonly used anti-inflammatory drugs, but long-term use can result in marked growth retardation in children due to their actions on growth plate chondrocytes. To gain an insight into the mechanisms involved in GC-induced growth retardation, we perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 72 publications
4
59
0
Order By: Relevance
“…Also known as neutrophil gelatinase-associated lipocalin (NGAL), Lcn2 is now recognized as an adipokine as it is predominantly produced by white adipose tissue [19]. Lcn2 has recently been identified in growth plate chondrocytes [20] where expression is modulated by IL-1b, leptin, adiponectin, lipopolysaccharides, and dexamethasone. The function of Lcn2 in cartilage and IVD tissue is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Also known as neutrophil gelatinase-associated lipocalin (NGAL), Lcn2 is now recognized as an adipokine as it is predominantly produced by white adipose tissue [19]. Lcn2 has recently been identified in growth plate chondrocytes [20] where expression is modulated by IL-1b, leptin, adiponectin, lipopolysaccharides, and dexamethasone. The function of Lcn2 in cartilage and IVD tissue is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of GCs has been rarely reported on chondrocytes, which play a key role in skeletal development. Sporadic studies have reported GC effects on the apoptosis and differentiation of chondrocytes (7,8). Autophagy is a lysosomal degradation process that is essential for cell growth, survival, differentiation, development and homeostasis (9).…”
Section: Introductionmentioning
confidence: 99%
“…LCN2 has recently been identified in chondrocytes (Owen et al, 2008). In these cells IL-1 , leptin, adiponectin, LPS and dexamethasone act as potent modulators of LCN2 expression (Conde et al, 2011).…”
Section: Lipocalinmentioning
confidence: 99%